Gender and law in the Japanese imperium - Burns, Susan L.; Brooks, Barbara J. (University of Hawaiʻi Press, 2014)
The Maria Luz incident and international justice--for Chinese coolies and Japanese prostitutes / Douglas Howland -- Disputing rights: the debate over anti-prostitution legislation in 1950s Japan / Sally A. Hastings -- Gender in the arena of the courts: the prosecution of abortion and infanticide in early Meiji Japan / Susan L. Burns -- Adultery and gender equality in modern Japan: 1868-1948 / Harald Fuess -- Of pity and poison: imprisoning women in modern Japan / Daniel Botsman -- Burning down the house: gender and jury in a Tokyo courtroom, 1928 / Darryl Flaherty -- Sim-pua under the colonial gaze: gender, "old customs," and the law in Taiwan under Japanese imperialism / Chao-ju Chen -- Japanese colonialism, gender, and household registration: legal construction of boundaries / Barbara J. Brooks -- An attempt to integrate the Korean family with the Japanese: a new perspective on the "name-changing policy" in Korea / Motokazu Matsutani
Includes bibliographical references and index
Keywords: Konferenzschrift -- 2006 -- Chicago, Ill.; Aufsatzsammlung; Konferenzschrift; Geschichte 1868-1960; Geschlechterverhältnis; Frauenbewegung; Japan